Robin Rönnlund, The Cities of the Plain: Urbanism in Ancient Western Thessaly. - Stissi, Vladimir (Journal of Greek Archaeology, 2025)
Besides his contributions to several fieldwork projects in Thessaly, Robin Rönnlund has produced a series of publications about sites, inscriptions and other finds from the region, also revisiting legacy data. The book reviewed here can be seen as a culmination of that work, at least for now. Soon after it came out it already made some headlines, after parts of its content and some of the more remarkable conclusions, and additional hypotheses based on them, were highlighted in an article in Antiquity.